Penguatan Tata Kelola Desa Simongagrok Mojokerto melalui Website Interaktif dan Informatif - Santosa, Santosa; Sutrisno, Eko; Amaliya , Nadiya; Utomo , Ardhian Danisvara; Rizkya , ⁠Fatikhatur; Setyawan , Doris (Penerbit Goodwood, 2025)
Purpose: imongagrok Village, Mojokerto, faces limitations in population data collection, transparency, public services, and access to information owing to the conventional administrative system. The lack of technology use causes slow information delivery and low community participation in village government. This service aims to strengthen the governance of Simongagrok Village by creating an interactive and informative website to increase transparency and public services. Methodology: The service activity was conducted in Simongagrok village, Dawarblandong District, Mojokerto, on October 9 and 30, 2024. The methods used included needs analysis, website development, village apparatus training, and evaluation of implementation effectiveness. The developed website has key features such as village information, online administration services, budget transparency, community aspiration forums, and local business directories. Results: Village websites enhance information access, budget transparency, administrative services, and two-way communication to support modern and accountable governance. Conclusions: The Simongagrok Village website has succeeded in increasing transparency, accelerating access to information, and simplifying administrative services in the village. Limitations: The low digital literacy of the community, limited Internet access in some areas, and lack of trained human resources to manage the village website sustainably. Contribution: This service activity is beneficial for village governance in Simongagrok, especially in the fields of e-government, information technology, and community participation, and can be applied in other rural areas to increase the transparency and efficiency of public services.